1997
DOI: 10.1039/a606881b
|View full text |Cite
|
Sign up to set email alerts
|

Spectrofluorimetric Determination of Vitamin K3 by a Solid-phase Zinc Reactor Immobilized in a Flow Injection Assembly

Abstract: The spectrofluorimetric determination of vitamin K3 (menadione) using a flow injection (FI) assembly provided with a solid-phase reactor with immobilized zinc is described. The naphthohydroquinone was produced by means of two coupled steps in the FI system: hydrolysis of the sodium sulfite derivative of the menadione in a basic medium and reduction of the generated menadione in the zinc reactor in an acidic medium. The fluorescent product was monitored spectrofluorimetrically (lambda ex 325 nm; lambda em 425 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Recently, Martínez Calatayud et al 16 reported a spectrofluorimetric determination of vitamin K 3 by using a flow injection assembly provided with a solid-phase reactor with immobilized zinc, where MSH was hydrolysed in alkaline medium and reduced by zinc in HCl medium. The limit of detection was 0.005 mg ml 21 .…”
mentioning
confidence: 99%
“…Recently, Martínez Calatayud et al 16 reported a spectrofluorimetric determination of vitamin K 3 by using a flow injection assembly provided with a solid-phase reactor with immobilized zinc, where MSH was hydrolysed in alkaline medium and reduced by zinc in HCl medium. The limit of detection was 0.005 mg ml 21 .…”
mentioning
confidence: 99%
“…17 The second method uses a flow injection assembly provided with a solid-phase reactor with immobilized zinc, where MSB is hydrolysed in alkaline medium and reduced by zinc in an acidic medium. 18 The reported detection limits were 4.4 3 10 29 and 2.9 3 10 28 mol l 21 , respectively. Both procedures were applied to the determination of menadione in pharmaceutical formulations.…”
Section: Introductionmentioning
confidence: 96%
“…Although the high sensitivity achieved by the fluorescence detection, quinones lack native fluorescence and have to be reduced to their hydroquinone form prior to fluorescence detection. Different procedures are used for quinone reduction, either chemically, [13][14][15] electrochemically 16 or photochemically 17,18 . Although the fluorescence detection may accomplish the required sensitivity, the methods lacked simplicity and rapidity because the reduction processes required many additional systems component such as reducing column, electric reactor or photoreactor.…”
Section: Introductionmentioning
confidence: 99%